General Worker’s Sleep Disturbances and the Degree of Cold-Heat Symptoms: a national cross-sectional survey - Min Kyung Hyun (Journal of Pharmacopuncture)
Objectives: Few studies have examined the impact of healthy sleep among general workers on individuals and society. Therefore, the status and risk factors of sleep disturbances among general workers were investigated. In addition, this study assessed the degree to which cold and heat symptoms are associated with sleep disturbances.Methods: A nationwide cross-sectional study was conducted through an online questionnaire focused on sleep disturbances of the general public in 2021. The degree of coldheat pattern Identification (CHPI) of the general public was also surveyed. Descriptive statistics and multivariate logistic regression were used to derive the study results.Results: Data from 2,822 workers out of 3,900 valid questionnaires were analyzed. Approximately half of the respondents (49.93%) had sleep disturbances. Among the types of work, self-employed, two-shift work, and working more than 53 hours were associated with sleep disturbances. Sleep disturbances were positively associated with six cold and heat symptoms: three cold symptoms (coldness of the abdomen, coldness of body, and pale face) and three heat symptoms (body feverishness, feverishness of the limbs, and drinking cold water).Conclusion: Customized policies to maintain healthy work are needed for self-employed work, two-shift work, and long working hours, which are risk factors for workers’ sleep disturbances. In addition, medical personnel can effectively diagnose and treat sleep disturbances considering the worker’s cold and heat symptoms.